Development of Learning Cycle 7E-Based Teaching Materials on the Topics of Cartesian Coordinates - Bela, Maria Editha; Wewe, Melkior; Suka, Felista Ripo (Jurnal Pendidikan MIPA, 2023)
Abstract: This research aims to develop and produce teaching materials. The teaching material in question is the Cartesian coordinates module for class VIII junior high school students. This Cartesian coordinate module is based on the 7e learning cycle model which meets valid and practical criteria. This research was carried out at SMP Negeri 5 Bajawa with the test subjects being class VIII students as potential product users. This development research uses the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The assessment instrument in this research uses expert test assessment sheets with the aim of measuring the level of validity of teaching materials as well as student and teacher response questionnaires with the aim of measuring the level of practicality of the teaching materials being developed. The research results show that the average validity score for teaching materials is 4.3 with the criteria "Very Good". Meanwhile, the average practicality score is 4.7 with the criteria "Very Good". Thus, the teaching material in the form of a Cartesian coordinate module based on the 7e learning cycle model for Class VIII middle school students is said to be valid and practical. Keywords: development, modules, ADDIE, cartesian coordinates and learning cycle 7E Abstrak: Penelitian ini bertujuan untuk mengembangkan dan menghasilkan bahan ajar. Bahan ajar yang dimaksud adalah Modul koordinat cartesius untuk Peserta didik SMP kelas VIII. Modul koordinat cartesius ini berbasis model learning cycle 7e yang memenuhi kriteria valid dan praktis. Penelitian ini dilaksanakan di SMP Negeri 5 Bajawa dengan subjek uji cobanya adalah peserta didik kelas VIII sebagai calon pengguna produk. Penelitian pengembangan ini menggunkan model pengembangan ADDIE yang terdiri dari lima tahapan yakni Analysis, Design, Development, Implementasi dan Evaluation. Instrumen penilaian dalam penelitian ini menggunakan lembar penilaian uji ahli dengan tujuan untuk mengukur tingkat kevalidan bahan ajar serta angket respon siswa dan guru dengan tujuan untuk mengukur tingkat kepraktisan bahan ajar yang dikembangkan. Hasil penelitian menunjukan rata-rata skor kevalidan bahan ajar adalah 4,3 dengan kriteia “Sangat Baik ”. Sedangkan rata-rata skor kepraktisan adalah 4,7 dengan kriteria “ Sangat Baik” . Dengan demikian bahan ajar berupa modul koordinat cartesius berbasis model learning cycle 7e untuk siswa SMP Kelas VIII dikatakan valid dan praktis.  Kata kunci: pengembangan, modul, ADDIE, koordinat cartesius dan learning cycle 7E. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp880-889